O ensino de funções na educação fundamental: o dito, o feito e o que pode ser feito - Machado, Raquel Fernandes Gonçalves (2005)
At First, the initial question of this paper was related to understand whether or not the Functions teaching should be developed on Fundamental School. However, when we began writing this paper we realized that before, we needed to answer something else; How understand the dynamics between the academic knowledge and the Functions Teaching on Fundamental School? Still, from this first question others came, considering the different factors that are directly or not interfering and integrating this subject s teaching skills. Our research includes some references to periods of the Mathematics Education s History, in order to understand the conceptions that are considered fundamentals to the current Functions Teaching. We also included some official documentation, as proposals from Minas Gerais and São Paulo, and to PCN (Parametros Curriculares Nacionais- National Curriculum Parameter), since we consider them important influence in teacher s actions and some of the authors of the subject. Our reflections had the valuable direct influence of Maria José and Doralina, both mathematics teachers, as well with the group of teachers that worked closer to us. By experiencing some moments of their professional routine, we were able to identify sources that help elaborate an answer to our question. A qualitative study is done in our paper, since we believed that subjectivity is present in numerous aspects, which is pointed out as meaningful to the answer to our question. So, we began the reflection about the meaning given to the subjects taught at this learning level that represents the foundation of a Functions concept elaboration. We realized the importance of this paper in revealing the actions of some education professionals, not only when the are directly involved with their students, but also when involved with the staff os education professionals of their school, since they represent important elements that influence and interfere each one. Nonetheless, we present our final considerations, believing them to be important contribution to understanding the dynamics of the different subjects teachers involved with the development of a subject in particular. It features some practical possibilities found at the mathematics modulate and also suggests about the initial formation of this academic that are believed to be truthful and able to be done.